Evaluasi dan Rekomendasi Implementasi Kanban Menggunakan Scaling Agile Berdasarkan CMMI 2: Studi Kasus PT XYZ - Muhammad Hezby Al Haq; Purwandari, Betty; Ferdinansyah, Alex (AI Society & STMIK Indonesia, 2025)
PT XYZ is financial technology company and operates in Southeast Asia. PT XYZ uses Kanban with more than 300 product and engineering employees with more than 20 teams. There are problems in software development, such as non standards in large scale Kanban practices used, communication between teams and dependencies between teams. Scaling Agile based on CMMI is a method that can be used to help identify problems in large-scale software companies where team-level Agile alone is not enough. The study discusses the evaluation of Kanban implementation at PT XYZ and recommendations for improving the software development process using Scaling Agile based on CMMI 2. The research uses qualitative data where interviews were conducted with Product Owners, Engineering Managers and Software Engineers. The results of the interviews were processed using the Key Process Area (KPA) rating. Finally, investigation produced 10 recommendations for the implementation of Kanban at PT XYZ.